Improving the prehospital management of ST elevation myocardial infarction: a national quality improvement initiative. Issue 2 (2nd June 2019) - Howard, Ian; Castle, Nicholas; Al Shaikh, Loua; Owen, Robert
Abstract : ST elevation myocardial infarction (STEMI) is a time-dependent clinical emergency. Early recognition and intervention in the clinical course of STEMI are key to reducing mortality and morbidity. As a result, the benefits of the prehospital management of patients presenting with STEMI are well supported by the literature. Given these benefits, much of the focus on the development of quality and performance measures for Emergency Medical Services has focused on STEMI care. Historically, within Qatar, however, no measures of prehospital STEMI care have previously existed and as such, little is understood regarding the quality of prehospital care delivered to patients with STEMI. The overall aim of this national initiative was to improve the effectiveness of the prehospital care of patients with STEMI, to a minimum compliance of 75%, as measured by four process measures and one bundle measure, over a 12-month period. Initial efforts were aimed at the development of relevant indicators to guide assessment and identifying an appropriate patient cohort to test improvement efforts. Using these measures and criteria, the project team highlighted several areas for potential improvement centred on three key domains within the service: clinical practice, training and clinical equipment/medication. There was significant and sustained improvement across all measures recorded. For the bundle measure, the median proportional compliance increased from 39% pre-improvement activities to 76% post-improvement activities and remained sustained at 12 months post-implementation. The initiative was successful in meeting all of its aims and furthermore showed sustained compliance at 12 months post-implementation, thanks in part to what were designed to be changes that were simple, yet pragmatic, and readily producible at scale. While a formal cost analysis was not conducted, the improvement activities capitalised on existing organisational structures and processes with the resultant cost perceived to be negligible.